Impacts of derivatives and managerial ownership on the financial performance of Shari'ah compliant firms - Zaminor Zamzamir@Zamzamin (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2021)
Most of the firms in the U.S, U.K, Australia and other developed countries have been using derivatives as an effective risk management instruments. Despite that, in Malaysia, many firms do not use derivatives as a risk management tool where the financial derivatives trading is low as compared to the neighboring countries as the use of derivatives by Malaysian is not comprehensive, derivatives are deemed to be complex and costly. Due to that, managers in Malaysia do not realise the advantages of taking positions in the derivatives market. Further, the firms are recognised as Shari’ah compliant firms, the risk management is still in the preliminary stage and the use of hedging instrument is found to be limited. This study covers 177 Shari’ah compliant firms that listed on Bursa Malaysia from 2000 to 2017, which 59 firms are the user of derivatives and the rest of 118 firms are non-users of derivatives. This study employs Logit Regression analysis to identify the users and non-users of derivatives. This study also employs the two-stage system GMM estimator for the total derivatives and foreign currency derivatives. While 2SLS GMM employs specifically for interest rate derivatives and commodity derivatives. This study finds Shari’ah compliant firms that are engaged in derivatives users seem to have performed better than non-users. Further, the results show that firm size, firms access to financial market, industry effect, and investment growth are the factors that influencing the decision to Shari’ah compliant firm to use derivatives. While managerial ownership and industrial diversification indicate negatively significant related to the probability of using derivatives. In the second part of analysis, it was extended to the performance context and impact on firms’ performance after the implementation of IFRS disclosure requirement. Using a two-step system GMM, the finding shows that derivatives has positive significant relationship with firm performance. Further, the third part of analysis, it was extended to non-linear relationship and interaction between derivatives use and managerial ownership. The analysis proved that a non-linear relationship exists between derivatives and firms performance of Shari’ah compliant firms. However, there is no non-linear relationship occurred for both interest rate derivatives and commodity derivatives on firms’ performance. Meanwhile, managerial ownership plays important role to engage in derivatives and eventually increase firm performance. This is based on the significant positive interaction between derivatives and managerial ownership. The results are also robust to different performance indicator of ROA, ROE and Probit regression. Overall, this study has important implications. The first is on the policymaker. The finding from this study has highlighted the importance of quality reporting on derivatives usage by firms and information symmetry in line with the required accounting standard on derivatives. The second is on Shari’ah compliant firms which highlight on the use of derivatives/hedging practices by Shari’ah compliant firms to reduce risk exposure, act as an effective tool for managing risk and to increase firm performance. Lastly, on the manager and shareholder where they will be able to design and strategize their derivatives activities to match the specific needs of the firms and also to reduce the risk exposures faced by the firms.